Effect of different settings and number of players on physiological and technical demands of ball-drills in basketball - Conte, D.; Favero, T.; Niederhausen, M.; Tessitore, A. (19th Annual Congress of the European College of Sport Science (ECSS), Amsterdam, 2. - 5. July 2014, 2014)
Introduction: Ball-drills (BD) are a training method that simultaneously develops basketball players` technical and tactical skills eliciting a high physical and physiological demand. Previous investigation focused on the effect of varying the number of players and court size on physiological and technical demands (Klusemann et al., 2012), while none analyzed the use of different BD settings in basketball. This study aimed to analyze the effect of different BD settings and number of players involved on players` physiological and technical demands. Methods: Twenty-one young basketball players belonging to under 17 and under 15 teams performed two different BDs: 3 bouts of 4 minutes played continuously (BDcont) and intermittently (alternating 1 minute of work and 1 of passive rest) (BDint). Each BD was played using a different number of players: 2vs2 and 4vs4. Training load (TL) was assessed through the rate of perceived exertion (RPE), percentage of maximal heart rate (%HRmax) and Edwards` TL (Edwards, 1993). Technical actions (TAs) were also collected and classified in: dribbles, passes, shots, interceptions, steals, rebounds and turnovers. A 2x2x3 (players x drills x bouts) 3-way ANOVA with repeated measures for %HRmax and a 2x2 (players x drills) 2-way ANOVA with repeated measures for Edwards` TL, RPE and TAs were applied. The level of statistical significance was set at p<0.05. Results: Results showed higher values (p<0.05) for %HRmax, Edwards TL and RPE in 2vs2 and BDcont compared to 4vs4 and BDint, respectively. A significant difference (p<0.05) was also showed among bouts for the %HRmax. Moreover, a significant difference (p<0.05) was found in the interaction of drills with players in the %HRmax and Edwards` TL, and in the interaction between players and bouts in the %HRmax. TA analysis showed higher (p<0.05) number of dribbles, passes, shots and rebounds in 2vs2 compared to 4vs4. Furthermore, dribble activity was performed more in BDint than in BDcont (p<0.05). Discussion: This study showed that a reduction of the number of players elicit higher physiological and technical demands. The BD setting comparison showed that BDcont stimulate greater physiological load, but a lower number of dribbles compared to BDint. Basketball coaches should vary the number of players involved and the BD settings to modify the BD workload intensity.